Network of Entamoeba histolytica HSP18.5 dimers formed by two overlapping [IV]‐X‐[IV] motifs. Issue 8 (8th April 2021) - Kurre, Devanshu; Suguna, Kaza
Abstract: Small heat shock proteins (sHSPs) are ATP‐independent molecular chaperones with low molecular weight that prevent the aggregation of proteins during stress conditions and maintain protein homeostasis in the cell. sHSPs exist in dynamic equilibrium as a mixture of oligomers of various sizes with a constant exchange of subunits between them. Many sHSPs form cage‐like assemblies that may dissociate into smaller oligomers during stress conditions. We carried out the functional and structural characterization of a small heat shock protein, HSP18.5, from Entamoeba histolytica ( Eh HSP18.5). It showed a pH‐dependent change in its oligomeric state, which varied from a tetramer to larger than 48‐mer. Eh HSP18.5 protected Nde I and lysozyme substrates from temperature and chemical stresses, respectively. The crystal structure of Eh HSP18.5 was determined at a resolution of 3.28 Å in C2221 cell with four subunits in the asymmetric unit forming two non‐metazoan sHSP‐type dimers. Unlike the reported cage‐like structures, Eh HSP18.5 formed a network of linear chains of molecules in the crystal. Instead of a single [IV]‐X‐[IV] motif, Eh HSP18.5 has two overlapping I/V‐X‐I/V sequences at the C‐terminus giving rise to novel interactions between the dimers. Negative staining Electron Microscopy images of Eh HSP18.5 showed the presence of multiple oligomers: closed structures of various sizes and long tube‐like structures.